Indoor air quality in gyms - a case study in the county of Coimbra - Monteiro, Fábio; Ferreira, Ana; Moreira, Fernando (Millenium - Journal of Education, Technologies, and Health, 2017)
Introduction: The appearance of the Indoor Air Quality (IAQ) as a Science appear in the 70's due to the energy crisis with consequent construction of private buildings. This vision only gained worldwide relief because of the discovery that a decrease in rates of air exchange in this type of buildings was the main cause for air increased pollutant concentration in the indoor air. Objetives: To evaluate the IAQ regarding the applicable legislation in gyms. Methods: The present study is characterized by being of level II, observational and cross-sectional cohort. The sample consisted of 3 gyms Coimbra and by 7 workers/. In order to achieve this objective, there was an analytical assessment of both physical and chemical parameters and filling questionnaires by the workers. Results: Regarding the obtained results of the evaluated parameters, it is possible to conclude that the PM 10 (Particulate Matter diameter of 10 mg/m3 ), the VOC's (Volatile Organic Compounds) and Relative Humidity presented risk values concerning workers health. Conclusions: The data collected it was possible to verify the importance and relevance of the studies in the future to ensure a better quality of life for all.